Numerical modelling of drilling of fiber reinforced polymer matrix composite: a review - Shinde, Avinash Sudam; Siva, Irulappasamy; Munde, Yashwant; Hameed Sultan, Mohamed Thariq; Lee, Seng Hua; Shahar, Farah Syazwani (Elsevier Editora Ltda, 2022)
Due to their superior advantage of strength-to-weight ratio, composite materials are mostly preferred over conventional materials. However, machining composite materials is a big challenge to industries due to their extreme heterogeneity. Several machining operations are required when the composites are brought to service; among all, drilling is one of the primary processes often required during assembling. Several researchers have done process parameter optimizations to attain improved quality drilling on composite materials. The experimental investigation involves a lot of effort, in terms of time and money, in the manufacturing and testing of the composites. With the invent of high-performance computing and its easy availability, in the recent past, researchers have started to work on the numerical simulation of the drilling process. The present review gives a comprehensive review of numerical modeling using finite element analysis of the drilling process for polymer composites. Numerical study on conventional and non-conventional drilling as well as orthogonal cutting with the effect of material, tool geometry, speed/feed, and temperature are reviewed. This will help the researchers to get a one-stop solution to learn different techniques used in numerical modeling of composite machining.